The efficacy of Lacticaseibacillus paracasei MSMC39-1 and Bifidobacterium animalis TA-1 probiotics in modulating gut microbiota and reducing the risk of the characteristics of metabolic syndrome: A randomized, double-blinded, placebo-controlled study - Wongsakorn Luangphiphat; Pinidphon Prombutara; Praewpannarai Jamjuree; Chantanapa Chantarangkul; Porntipha Vitheejongjaroen; Chantaluck Muennarong; Krittapat Fukfon; Manasvin Onwan; Malai Taweechotipatr (PLoS ONE, 2025)
Modern treatment, a healthy diet, and physical activity routines lower the risk factors for metabolic syndrome; however, this condition is associated with all-cause and cardiovascular mortality worldwide. This investigation involved a randomized controlled trial, double-blind, parallel study. Fifty-eight participants with risk factors of metabolic syndrome according to the inclusion criteria were randomized into two groups and given probiotics (Lacticaseibacillus paracasei MSMC39-1 and Bifidobacterium animalis TA-1) (n = 31) or a placebo (n = 27). The participants had a mean age of 42.29 ± 7.39 and 43.89 ± 7.54 years in the probiotics and placebo groups, respectively. Stool samples, anthropometric data, and blood chemistries were taken at baseline and at 12 weeks. The primary outcome was achieved by the probiotics group as their low-density lipoprotein-cholesterol level dramatically lowered compared to the placebo group (the difference was 39.97 ± 26.83 mg/dl, p-value <0.001). Moreover, significant reductions in body weight, body mass index, waist circumference, systolic blood pressure, and total cholesterol were observed in the volunteers treated with probiotics compared to the placebo. In the gut microbiome analysis, the results showed statistically significant differences in the beta diversity in the post-intervention probiotics group. Blautia, Roseburia, Collinsella, and Ruminococcus were among the gut microbiomes that were more prevalent in the post-intervention probiotics group. In addition, this group exhibited increases in the predicted functional changes in ATP-binding cassette (ABC) transporters, as well as ribonucleic acid transport, the biosynthesis of unsaturated fatty acids, glycerophospholipid metabolism, and pyruvate metabolism. In conclusion, this research demonstrated that the probiotics L. paracasei MSMC39-1 and B. animalis TA-1 have the efficacy to lower risk factors associated with metabolic syndrome.